The electoral profile and its influence on the voting decision: municipal elections in Lima 2010 - Saavedra Pacheco, José (2010)
Why does the reader vote the way he/she votes? Voter satisfaction in choosing a candidate encompasses a series of indicators and makes this variable multidimensional in nature. In order to construct the electoral profile index, factor analysis is used, which takes into account the difference between what the reader expects and what he/she perceives in the electoral process. This study establishes the main determinants of the voter's decision process in Metropolitan Lima and then constructs an indicator of the corresponding electoral profile.